The mapping of ovarian cancer mortality trends in Brazil (Research, Society and Development, 2020)
Ovarian cancer is the eighth cause of death by cancer in women worldwide. The objective of this study was to analyze trends in the Brazilian ovarian cancer mortality and the relation to age, schooling, and race. Data was collected in the Brazilian Mortality Information System (SIM), from 2006 to 2016. The polynomial regression model was used for the trends analysis, a significant trend was considered when the estimated model obtained a p-value